2015
DOI: 10.1039/c5tx00052a
|View full text |Cite
|
Sign up to set email alerts
|

New approaches for biomonitoring exposure to the human carcinogen aristolochic acid

Abstract: Aristolochic acids (AA) are found in all Aristolochia herbaceous plants, many of which have been used worldwide for medicinal purposes for centuries. AA are causal agents of the chronic kidney disease entity termed aristolochic acid nephropathy (AAN) and potent upper urinary tract carcinogens in humans. AAN and upper urinary tract cancers are endemic in rural areas of Croatia and other Balkan countries where exposure to AA occurs through the ingestion of home-baked bread contaminated with Aristolochia seeds. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 80 publications
(245 reference statements)
1
34
0
Order By: Relevance
“…The uncertainty in labeling efficiency and the lack of physiochemical structural confirmation puts DNA adduct analysis by 32 P-postlabeling methods into question. 28,29 …”
Section: Introductionmentioning
confidence: 99%
“…The uncertainty in labeling efficiency and the lack of physiochemical structural confirmation puts DNA adduct analysis by 32 P-postlabeling methods into question. 28,29 …”
Section: Introductionmentioning
confidence: 99%
“…However, the need to confirm adduct structure by a higher level of fragmentation of the adducted base or higher resolving power have turned researchers to other mass analyzers such as ion trap (IT) or time-offlight (TOF; Tretyakova et al, 2012). Our laboratory has extensively used IT-MS employing the multi-stage scanning (MS n ) feature to screen for DNA adducts present at trace levels in humans (Goodenough et al, 2007;Gu et al, 2012;Yun et al, 2015).…”
Section: Methods To Measure Dna Adductsmentioning
confidence: 99%
“…This method built the foundation for a series of publications on the measurement of aristolactam DNA adducts in fresh frozen but also in formalin‐fixed paraffin‐embedded (FFPE) renal tissues, and exfoliated urothelial cells. Employing HPLC‐LIT‐MS 3 , dA‐AL‐I was quantified in renal cortex and upper urothelial tumor tissues from nearly 200 patients with upper urothelial cancer from Taiwan, the Balkan endemic regions, and Romania (Yun et al., , , , ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our laboratory in conjunction with collaborators at Stony Brook University and Peking University First Hospital, Beijing, China, showed that the DNA adduct of aristolochic acids, dA‐AL‐l, can be measured in DNA of EUC from patients with renal disease and a known history of ingestion of traditional Chinese medicines. The DNA adduct measurements were conducted by UPLC‐ESI‐IT‐MS on EUC specimens collected for 12 or 24 hr . The recovery of DNA ranged between 11 and 33 μg, a level that was sufficient to measure the dA‐AL‐I at levels above LOQ value, three adducts per 10 9 bases, with only two μg of DNA required for assay.…”
Section: Formalin‐fixed Paraffin‐embedded Tissues: Untapped Biospecimmentioning
confidence: 99%
“…Recent studies have also shown that DNA obtained from exfoliated oral cells can be used to screen for DNA adducts of carcinogens present in tobacco smoke, cooked meat, and ethanol by MS‐based methods . Thus, current LC/MS instruments have the required sensitivities to screen for many DNA adducts in human biospecimens.…”
Section: Formalin‐fixed Paraffin‐embedded Tissues: Untapped Biospecimmentioning
confidence: 99%